Efektivitas Penerapan Model Pembelajaran CTL Dalam Meningkatkan Hasil Belajar Matematika Siswa Pada Kelas III SD Inpres Timika IV - Godeliva Maria Goreti Bulu (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to improve mathematics learning outcomes in class III of SD Inpres Timika IV. This research is classroom action research carried out collaboratively with the class teacher and supervisor. Learning mathematics on the main subject of fractions using the CTL learning model can improve the learning outcomes of class III students at SD Inpres Timika IV. The increase in student learning outcomes can be seen from the increase in students' written test scores in the pre-cycle, cycle I and cycle II. The average test score in the pre-cycle was 58.40, increasing to 73.80 in cycle I, then in cycle II it increased to 85.80. In cycle I, there was a difference with the pre-cycle results. Of the 25 students, only 8 students (32%) got grades according to the KKM in the pre-cycle. Then, after the first cycle of action, this increased to 20 students (80%) who received grades according to the KKM. After the second cycle of actions, students who received grades according to the KKM increased again to 22 students (88%). The use of the CTL learning model in improving student learning outcomes in cycle II, the percentage of classical learning completeness has reached >75% so that the learning process using the CTL learning model is successful.